2020
DOI: 10.1038/s41598-020-77850-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pseudomonas sp. for its multifarious plant growth promoting potential and its ability to alleviate biotic and abiotic stress in tomato (Solanum lycopersicum) plants

Abstract: Abstract1-Aminocyclopropane-1-carboxylate (ACC) deaminase activity is one of the most beneficial traits of plant growth promoting (PGP) rhizobacteria responsible for protecting the plants from detrimental effects of abiotic and biotic stress. The strain S3 with ACC deaminase activity (724.56 nmol α-ketobutyrate mg−1 protein hr−1) was isolated from rhizospheric soil of turmeric (Curcuma longa), a medicinal plant, growing in Motihari district of Indian state, Bihar. The halotolerant strain S3, exhibited optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 84 publications
2
26
0
Order By: Relevance
“…Other studies reported similar plant growth-promoting and antifungal effects of the isolated strains of Pseudomonas sp. [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported similar plant growth-promoting and antifungal effects of the isolated strains of Pseudomonas sp. [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A Pseudomonas sp. S3 isolated from turmeric rhizosphere enhanced proline content and profoundly increased TSS in tomato under salt stress ( Pandey and Gupta, 2020 ). Increased levels of TSS in maize inoculated with Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The dual culture assay (Pandey and Gupta 2020) was used for the evaluation of the antagonistic activity of the strain S. chilikensis RC1830 against phytopathogenic fungi F. oxysporum . The S. chilikensis RC1830 was streaked in a straight line on four edges around the fungal mycelia streaked at the centre of a PDA plates and incubated at 25°C for 4 days.…”
Section: Methodsmentioning
confidence: 99%